Solar energy for all? Understanding the successes and shortfalls through a critical comparative assessment of Bangladesh, Brazil, India, Mozambique, Sri Lanka and South Africa. (February 2019) - Kumar, Ankit; Ferdous, Raihana; Luque-Ayala, Andrés; McEwan, Cheryl; Power, Marcus; Turner, Britta; Bulkeley, Harriet
Abstract: Lanterns, homes systems, hot water systems and micro-grids based on small-scale solar have become prominent ways to address the energy access challenge. As momentum grows for this form of energy transition this paper draws together research on small-scale solar in six different countries – Bangladesh, Brazil, India, Mozambique, Sri Lanka and South Africa – to argue for a need to understand how, when, and for whom solar provides energy access. It argues that an assemblage perspective can provide vital insights into the diversity and dynamism of energy access. The paper demonstrates that the diverse ways in which solar provides energy access is a function of the flexibility/fixity of the socio-technical assemblage and the de/centralisation of agency. The central thesis of this paper is that energy access is fluid and ever changing and we need fluid, easily maintainable, locally modifiable 'assemblages' for providing such access. Using this perspective, we find three common features of solar energy access across our case studies. First, there are significant gaps between what solar projects are designed to achieve and what they deliver, which are highly contingent on the flexibility of their structure and the decentralisation of agency within them. Second, access needs to endure continuously. Third, to foster enduring access, projects should embed logics of improvisation. This paper is based on six separate qualitative research projects conducted during 2010–2016. It draws data from 482 interviews, 91 home tours and 12 group discussions.